Effect of sintering temperature on phase transition and mechanical properties of lead zirconate ceramics - Puchmark C. (2014)
Phase transition and mechanical properties of PbZrO3 (PZ) at different sintering temperatures were studied. The Curie temperature depends on the sintering temperature. Hardness and fracture toughness of the PZ were measured using Vickers and Knoop microhardness testers. The lower density at the higher sintering temperature resulting from the loss of lead oxide (PbO) causes the lower value of the Curie temperature, hardness and fracture toughness. The results were well corresponding to the microstructure of the PZ ceramics.